Conveyance and the moderating effect of envy on homeowners' choice of appliances - Joachim Schleich; Corinne Faure; Marie-Charlotte Guetlein; Gengyang Tu (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2019)
Conveyance, i.e., the fact that an appliance purchased will be left in the dwelling when moving out, may lead homeowners to purchase appliances of lower quality or performance, because the extra costs are not entirely capitalized into the house sales price. Employing a discrete choice experiment with homeown-ers in the United States, this paper explores the effects of conveyance on homeowners' willingness-to-pay for various attributes of refrigerators. To ac-count for the social nature of purchases when conveyance is likely to occur, it also tests the moderating role of envy (elicited through an incentivized game). The findings suggest that conveyors are more likely to purchase a smaller re-frigerator, from a less well-known brand, and with lower customer ratings. In contrast, conveyance was not found to affect homeowners' choices when it comes to energy cost. In addition, envy was found to generally reinforce the negative effects of conveyance on homeowners' willingness-to-pay for quality and performance attributes. While conveyance and its interaction with envy help explain homeowners' choice of quality/performance attributes of applianc-es, these factors do not appear to explain the energy efficiency paradox.
urn:nbn:de:0011-n-5527150
Keywords: 330; energy efficiency paradox; conveyance; envy; choice experiment